Mutu sabun transparan ekstrak etanol herba pegagan (Centella asiatica L.) setelah penambahan sukrosa - Andarini Siwi Mumpuni; Heru Sasongko (Universitas Ahmad Dahlan, 2017)
Centella asiatica L. is a kind of herbs which contains antioxidant that be trusted to overcome of various skin problems such as keloids, cellulite, and black stains. One of the additional ingredients used to make the transparent soap is sucrose or frequently called white sugar. In the process of making the transparent soap, white sugar is served to help the transparency of soap. The purpose of this research is to find out the effect of increasing the sucrose toward the degree of the transparency of the soap, stability of physical properties before and after storage for eight weeks and find out the skin response towards the soap by doing irritability test towards some respondents. Pegagan extract transparent soap is varied with the concentration of sucrose 11 %, 13%, and 15 %. The soap which is produced is conducted with a series of tests of physical characteristics include transparency, pH, water content, and the stability of the foam. The results showed that the addition of sucrose affect the increase in the level of transparency of the soap. Variations of sucrose concentration do not affect the pH value and stability of the foam (> 0.05). Physical properties and chemical stability for 8 weeks showed no significant difference except soapy water content ranged from 0.00 - 0.046 significance value <0.05